Examining linkages among multiple sustainable development outcomes: Does the productive safety net program increase on‑farm agrobiodiversity? - Kozicka, Marta; Gotor, Elisabetta; Pagnani, Tiziana; Occelli, Martina; Caracciolo, Francesco (Springer, 2023)
play a key role in building smallholders’ resilience. However, the impact of PSNP on on- farm agrobiodiversity is not yet well investigated. In this paper, we develop an analytical framework that links PSNP participation to on-farm agrobiodiversity. Both diverse farm- ing systems and PSNP require labour inputs while providing income stabilization, which might result in a negative relationship between the two. Conversely, higher income from PSNP might allow farmers to increase their long-term on-farm investments, as opposed to the strategies oriented toward the highest immediate profit or calorie intake outcome. We base our empirical analysis on the World Bank’s Ethiopian Socioeconomic Survey, a panel dataset encompassing nearly 3000 respondents and a Tobit model, based on Difference-in- Difference and the Propensity-Score Matching methods. We find that Ethiopia’s PSNP has a negative impact on farm labour input, both in terms of labour intensity and duration. Fur- thermore, our results show that participation in the program is associated, on average, with lower on-farm crop diversity. We conclude that the PSNP participation may be crowding- out production stabilizing farming activities, such as intercropping or cover cropping, that are more labour intensive. Our findings call for embedding tools in the new phase of the PSNP (2021–2025) that could incentivise on-farm resilience-oriented investments, in par- ticular leading to higher crop diversification.